Chromatin architectural alterations due to null mutation of a major CG methylase in rice. Issue 12 (7th November 2022) - Wang, Jinbin; Li, Xiaochong; Dong, Qianli; Li, Changping; Li, Juzuo; Li, Ning; Ding, Baoxu; Wang, Xiaofei; Yu, Yanan; Wang, Tianya; Zhang, Zhibin; Yu, Yiyang; et al.
Abstract: Associations between 3D chromatin architectures and epigenetic modifications have been characterized in animals. However, any impact of DNA methylation on chromatin architecture in plants is understudied, which is confined to Arabidopsis thaliana . Because plant species differ in genome size, composition, and overall chromatin packing, it is unclear to what extent findings from A. thaliana hold in other species. Moreover, the incomplete chromatin architectural profiles and the low‐resolution high‐throughput chromosome conformation capture (Hi‐C) data from A. thaliana have hampered characterizing its subtle chromatin structures and their associations with DNA methylation. We constructed a high‐resolution Hi‐C interaction map for the null OsMET1‐2 (the major CG methyltransferase in rice) mutant ( osmet1‐2 ) and isogenic wild‐type rice (WT). Chromatin structural changes occurred in osmet1‐2, including intra‐/inter‐chromosomal interactions, compartment transition, and topologically associated domains (TAD) variations. Our findings provide novel insights into the potential function of DNA methylation in TAD formation in rice and confirmed DNA methylation plays similar essential roles in chromatin packing in A. thaliana and rice. Abstract : Hi‐C data in null mutants of the CG methyltransferase MET1 from rice and Arabidopsis confirmed that DNA methylation plays an important and conserved role in 3D chromatin packing and has possible significance in topologically associated domain formation in rice.